Evaluasi Pengelolaan Sistem Informasi Pelayanan Perizinan (SIPPERI) dalam Meningkatkan Kualitas Pelayanan Izin Praktik Dokter di Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu (DPMPTSP) Kota Palembang - Pitaloka Tri Anggoro; Bachtari Alam Hidayat; Raniasa Putra (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2025)
The Management of the Licensing Service Information System (SIPPERI) at the Palembang City Investment and One-Stop Integrated Services Office (DPMPTSP) has contributed to the digitization of licensing services, especially in the issuance of medical practice licenses. This study used the CIPP (Context, Input, Process, Product) evaluation model to assess the effectiveness of the system’s implementation. Data were collected through interviews with seven informants selected using purposive sampling. From the context aspect, the development of SIPPERI has answered the demands of bureaucratic reform, but the lack of understanding of information technology among medical personnel is an obstacle. From the input aspect, the digital infrastructure is quite adequate, but technical support and user training are still limited. From the process aspect, digital procedures have not been fully accompanied by optimal socialization and mentoring, thus hindering the effective use of the system. From the product aspect, SIPPERI makes administration easier, but it does not meet service time standards due to input errors and lack of technical guidance. These findings show that although SIPPERI has great potential in improving the efficiency of doctor’s practice license services, continuous improvement efforts are still needed through strengthening user capacity, increasing digital literacy, and improving the overall system to realize faster, more effective, and quality public services.